DESIGN OF ACCOUNTING RECORDING SYSTEM BASED ON MICROSOFT OFFICE ACCESS AT TOKO ASLI MOTOR - Serly Serly; Andy Lau (ConCEPt - Conference on Community Engagement Project, 2022)
Toko Asli Motor is a small and medium enterprises that operates as an automotive sparepart distributors. Toko Asli Motor still using an inaccurate and inefficient accounting record. The accounting record of Toko Asli Motor was stored manually in microsoft excel and only record the number of sales based on issued invoices. Accounting record system from Toko Asli Motor couldn’t produce an accurate financial statement. Toko Asli Motor yet to record inventory mutations, therefore problem usually occurs when confirming the amount of inventory left in the store. The purpose of this community services is to design an accounting recording system which can produce accurate financial statements and also other supporting reports.The beginning proccess is to accumulate bunch of datas regarding Toko Asli Motor by using observations and interviews. The accumulated data later will be used to analyze problems and needs from Toko Asli Motor in accounting records. The next step is the designing step of accounting record system in accordance with the needs of Toko Asli Motor. The finished system will be given to Toko Asli Motor and later on will conduct training of how to use the system. Designed system aims to fix previous accounting record of Toko Asli Motor. For the next community services, a more complex and in accordance with applicable financial accounting standards is to be expected.